Involvement of the L-DOPA receptor GPR143 in acute and chronic actions of methylphenidate - Hiraku Uchimura; Kaori Kanai; Masami Arai; Miyu Inoue; Akitoyo Hishimoto; Daiki Masukawa; Yoshio Goshima (Journal of Pharmacological Sciences, 2023)
Methylphenidate (MPH) and methamphetamine (METH) are the current treatments of choice for attention deficit/hyperactivity disorder. We previously reported that METH induces the release of dopamine (DA) and of the neurotransmitter candidate L-3,4-dihydroxyphenylalanine (L-DOPA). In contrast, we here found that MPH increased the DA release while it did not affect the L-DOPA release from the dorsolateral striatum. Nevertheless, MPH-induced hyperlocomotion was reduced in Gpr143 (L-DOPA receptor) gene-deficient (Gpr143−/y) mice. The rewarding effect and increased c-fos expression induced by MPH were also attenuated in Gpr143−/y mice. Together, these findings suggest that GPR143 is involved in the acute and chronic actions of MPH.